Discovery of Novel Thiazol-2-Amines and Their Analogues as Bioactive Molecules: Design, Synthesis, Docking and Biological Evaluation - Verma, Anil Kumar; Bishnoi, Abha; Fatma, Shaheen; Parveen, Huda; Singh, Vineeta (Drug Research, 2018)
A simple and highly efficient procedure for the synthesis of novel thiazol-2-amines, via Mannich reaction with secondary amines, is described. The newly synthesized derivatives 8(a-e) and 9(a-e) were characterized by 1H NMR, 13C NMR, IR, Mass spectroscopy and elemental analysis. All the derivatives were evaluated for their in-vitro anti-microbial activity against a panel of pathogenic strains of bacteria and fungi. The SAR showed that the secondary amines had a significant impact on the in-vitro antimicrobial activity of this class of agents. The most potent analogue N-((1H-benzo[d]imidazol-1-yl)methyl)-N-(2(trifluoromethyl)phenyl)-4,5-dihydrothiazol-2-amine (8c) showed excellent inhibition with MIC (zoi) 6.25 (22.5), 25 (21.5) and 25 (18) µg/mL against E. coli, S. typhi and P. aeruginosa respectively as compared to the standard drug. Molecular docking results suggest that compound exhibited inhibitory activity by binding of the title compound within the active sites of the inhibiting Enoyl ACP reductase, Lipid A, Pyridoxal kinase and type I DHQase enzymes. The compound exhibited promising anti-microbial activity which can be further explored as potential lead for the development of cheaper, safe, effective and potent drugs against resistant microbial parasites.
Keywords: Benzimidazole moiety; Mannich reaction; Molecular Docking